Expression of a new Bacillus thuringiensis Cry1Ia gene in Escherichia coli with strong activity against cotton pests - Bergamasco, V. B. [UNESP]; Gonçalves, J. F. [UNESP]; Polanczyk, R. A. [UNESP]; Desidério, J. A. [UNESP]; Lemos, Manoel Victor Franco [UNESP] (My University, 2011)
The control of cotton pests may be accomplished using Bacillus thuringiensis Cry proteins. For this purpose, the objective of this work was to evaluate the insecticidal activity of a new Cry1Ia protein against neonatal larvae of Spodoptera frugiperda and Anthonomus grandis. The complete cry1Ia gene, previously obtained by PCR with oligonucleotide primers based on the sequenced gene, was cloned into the vector pET28a(+), introduced into Escherichia coli BL21(DE3) and expressed by induction with IPTG. The expression of the Cry1Ia protein was confirmed with molecular weight of approximately 81 kDa. The results demonstrated the efficiency of the bacterial system for the expression of B. thuringiensis Cry1Ia protein, which was subsequently used in quantitative bioassays against S. frugiperda and A. grandis larvae, resulting in an extremely toxic protein for both species. This characteristic is exceptionally important for obtaining transgenic cotton plants resistant to these pests.
Keywords: Anthonomus grandis; Coleoptera; Cry Genes; Lepidoptera; Spodoptera frugiperda